Agro-morphological traits-based genetic diversity assessment on oat (Avena sativa L.) genotypes in the central highlands of Ethiopia - Gezahagn Kebede; Walelign Worku; Fekede Feyissa; Habte Jifar (All Life, 2023)
The study aimed to estimate the extent of genetic variability, heritability, and expected genetic gain attributable to agro-morphological traits and to suggest an effective selection scheme and specify promising genotypes for future oat breeding programs. One hundred twenty oat (Avena sativa L.) genotypes were evaluated at two locations in the central highlands of Ethiopia. The analysis of variance indicated that the mean squares due to locations and genotype x location interaction varied significantly for some measured traits while that of genotypes varied significantly (P ≤ 0.001) among all studied traits. Moreover, the estimates of genetic variability, heritability, and expected genetic advance indicate the presence of remarkable genetic diversity in oat genotypes and the magnitude of selection response for these traits in the population to develop superior genotypes for oat improvement. The result revealed that very high to moderately high heritability in a broad sense (h2b) coupled with high to moderate genetic advance as percent of mean (GAM) were recorded for forage dry matter yield (h2b = 64.4%; GAM = 19.3%), number of leaves at forage harvest (h2b = 86.4%; GAM = 19.9%), stem dry matter yield (h2b = 62.9%; GAM = 18.3%), forage yield production rate (h2b = 69.7%; GAM = 21.7%), grain yield (h2b = 64.2%; GAM = 26.1%), panicle length at grain harvest (h2b = 80.9%; GAM = 21.9%), number of spikes per panicle (h2b = 68.8%; GAM = 16.0%), and harvest index (h2b = 80.9%; GAM = 26.0%). The results suggested that these traits are governed more by additive gene action, and selection based on these traits could be effective to achieve the desired genetic gains for improvement. Therefore, high forage dry matter and grain yielding genotypes along with these desirable yield-related traits could be considered for selection in oat genotypes.